BEST PRACTICES IN THE USE OF MOBILE LEARNING BY UNIVERSITY TEACHERS OF DIDACTICS LANGUAGE-LITERATURE - Romero-Rodríguez, José-María; Aznar-Díaz, Inmaculada; Trujillo-Torres, Juan-Manuel; Moreno Guerrero, Antonio José (Revista Conhecimento Online: Diversidade e Inclusão Social, 2021)
The use of mobile learning is becoming increasingly widespread among university teachers, thanks to its many benefits. Moreover, its application is associated with good teaching practices. The aim of this study is to analyse the development of good teaching practices in the use of m-learning by university teachers from the Department of Didactics of Language and Literature, as well as to identify the factors that influence the development of best practices. The research method developed is based on a transversal design. 110 teachers from the Department of Language and Literature Didactics participated in the study. The instrument used is the scale of Analysis of M-learning practices at the University (APMU). The results show that more than half of the teachers use the teaching method based on mobile learning. It can be concluded that in the development of best practices, gender is not influential, but age and teaching experience are. In addition, personal concern and experience in the use of mobile devices by teachers is a key factor in the appropriate development of the m-learning method.